Analisis Perlindungan Hukum terhadap Data Konsumen Marketplace di Indonesia Berdasarkan Undang-undang No 27 Tahun 2022 - Zendik Anggriawan; Ratih Kemala; Erry Praditya (HUMANIORUM, 2023)
One of the legal problems in Indonesia is the lack of clarity and protection of consumer privacy and personal data because Indonesia does not yet have specific legal regulations to meet the public's need for better protection in the field of privacy and personal data. The inability of Indonesian law to keep up with developments in information technology can negatively impact the community's ability to run e-commerce. Indonesia still has deficiencies in two aspects, namely the consumer protection aspect and the privacy aspect. In this journal, the authors choose to apply a normative juridical method with a conceptual approach and a statutory approach related to the legal protection of marketplace consumer data. The technique of tracing legal materials uses a literature study technique as well as an analysis of the study using qualitative analysis. Based on the results of the discussion, the authors can conclude that legal protection for marketplace consumer data in Indonesia has been regulated in Law No. 27 of 2022 since October 17, 2022. This law is the main basis for dealing with rights violations related to personal data. This regulation was drafted to prevent conflicts between regulations and ensure the protection of personal data for the public. Article 1 describes general regulations related to personal data protection, while Article 57 regulates administrative sanctions that will be given if violations continue. Article 67 also explains criminal provisions related to violations of personal data.